Toll-like receptor signalling associated with immunomodulation of umbilical cord–derived mesenchymal stem cells in mice with systemic lupus erythematosus. (February 2020) - Wu, K H; Cheng, C C; Li, J P; Weng, T F; Yang, S F; Pan, H H; Chao, Y H
With potent immunomodulatory activities, mesenchymal stem cells (MSCs) have the potential to be a beneficial treatment option for diseases with aberrant immune responses such as systemic lupus erythematosus (SLE). However, the underlying mechanisms remain largely unknown. Here, we used NZBWF1 mice as a SLE animal model to examine immunomodulation of MSCs as well as to assess the role of Toll-like receptor signalling in this circumstance. We found that mice receiving MSCs had a significant decrease in severity of proteinuria at 20 and 22 weeks of age ( p  = 0.009 and p  = 0.022, respectively). Serum anti-dsDNA levels were significantly lower compared with the control group ( p  = 0.016 and p  = 0.036, respectively). C3 and C4 levels were significantly higher at 22 weeks of age ( p  = 0.046 and p  = 0.016, respectively). Altered expression of inflammation-associated cytokine profiles in the serum was also noted in mice receiving MSCs. Down-regulation of myeloid differentiation factor 88 (MyD88)-nuclear factor-κB (NF-κB) signalling in the liver was demonstrated by quantitative polymerase chain reaction, ELISA and Western blotting. In addition to demonstrating the beneficial effects of MSC treatment in NZBWF1 mice, our study provided the first evidence for the association of MyD88-NF-κB signalling and MSC-mediated immunomodulation in this disease.